2011
DOI: 10.1016/j.virol.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Escape from R-peptide deletion in a γ-retrovirus

Abstract: The R peptide in the cytoplasmic tail (C-tail) of γ-retroviral envelope proteins (Env) prevents membrane fusion before budding. To analyse its role in the formation of replication competent, infectious particles, we developed chimeric murine leukaemia viruses (MLV) with unmodified or R-peptide deleted Env proteins of the gibbon ape leukaemia virus (GaLV). While titres of these viruses were unaffected, R-peptide deficiency led to strongly impaired spreading. Most remarkably, we isolated an escape mutant which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, while the production of LVs pseudotyped with 4070A has no impact on infectious titers,23, 24, 25, 26, 27 the co-expression of HIV-1 core proteins with GaLV or RD114 glycoproteins barely results in the production of infectious LVs 28, 29, 30, 31, 32. These titer asymmetries are due to differences between cytoplasmatic tail amino-acid sequences of the glycoproteins (Figure 1A), since the fully fusogenic activation of 4070A, RD114, and GaLV is dependent on the cytoplasmatic tail R-peptide recognition and cleavage by the viral protease 33, 34, 35, 36, 37, 38, 39, 40, 41, 42. The replacement of the RD114 and GaLV cytoplasmic tail region by the one for 4070A (originating the RD114-TR and GaLV-TR, respectively) allows a high increase of LV particle infectivity 19, 23, 28, 29, 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the production of LVs pseudotyped with 4070A has no impact on infectious titers,23, 24, 25, 26, 27 the co-expression of HIV-1 core proteins with GaLV or RD114 glycoproteins barely results in the production of infectious LVs 28, 29, 30, 31, 32. These titer asymmetries are due to differences between cytoplasmatic tail amino-acid sequences of the glycoproteins (Figure 1A), since the fully fusogenic activation of 4070A, RD114, and GaLV is dependent on the cytoplasmatic tail R-peptide recognition and cleavage by the viral protease 33, 34, 35, 36, 37, 38, 39, 40, 41, 42. The replacement of the RD114 and GaLV cytoplasmic tail region by the one for 4070A (originating the RD114-TR and GaLV-TR, respectively) allows a high increase of LV particle infectivity 19, 23, 28, 29, 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…When the R-peptide was removed from a gammaretroviral Env it spread poorly in cell culture, but given time it acquired a compensatory extension of the C-terminus. This also restored the colocalization between the envelope protein and Gag, implying an additional role for the R-peptide in assembly of viral particles [ 170 ]. The R-peptide of MLV, and the entire cytoplasmic tail, is dispensable for assembly with HIV particles, consistent with the fact that HIV glycoproteins do not contain an R-peptide.…”
Section: Hallmark Features Of Gamma-type Envsmentioning
confidence: 99%
“…As mentioned before, CT interactions with the viral core may play an important role in glycoprotein incorporation. It was shown that most mammalian and avian retroviruses such as HIV, MLV and ALV (avian leukemia virus) require proteolytic cleavage of the R-peptide, a short amino acid sequence (16 aa) at the C-terminus of CT of the envelope glycoprotein for activation (Bobkova et al, 2002;Green et al, 1981;Henderson et al, 1984;Schneider et al, 2011).…”
Section: Figure 6: Pseudotyping Of Lentiviral Vectorsmentioning
confidence: 99%